Requadro feminino: feminilidade e gênero a partir da tira Aline de Adão Iturrusgarai - Giongo, Fernanda Aparecida (2018)
This research aims to analyze the possibility of thinking about the notions of femininity, hegemonic or not, as a feminine characteristic through the comics trip Aline, drawn by cartoonist Adão Iturrusgarai and published in the Folha de São Paulo newspaper between the years of 1996 and 2004. It is proposed a discussion about the femininity presented by the maincharacter, Aline, who presentes diferente characteristics from those preconceived for the formation of the 'being' woman, and in what way the behaviors of the character dialogue with expressions of the feminist fight at the end of the XX century and early XXI century such as the search for the sexual pleasure and the right to the sovereignty of the self body. The theoretical basis is Michel Foucault's analysis in History of Sexuality I, showing sexuality as a subjective characteristic of subjects, which marks the identities and relations of power based on the ruled discourses that rules and shape these identities. The analysis is also based on authors such as Judith Butler and Simone de Beauvoir to deal about the femininity as a social and identitary construction. Thanks to the representativeness of The political character that comics trips have, and also to being easily accessible cultural products, this research uses them as object of analysis. The comicstrip, especially the strip Aline, allows you to think specific questions about sexuality, femininity and feminism.